Three objects calalogued as vantsöm in the collections of the Museum der Kulturen in Basel, Swizerland - Karp, Cary; Decker, Anne Marie (Archaeological Textiles Review, 2022)
The looped structure termed a slip stitch in the craft glossary of crochet can be produced both with a hook and an eyed needle. These implements are not equally amenable to working this structure into complex constructs such as the toe and heel of a sock. This article describes the examination of three objects that have been misidentified as nalbinding. Two of them are certain to have been crocheted and the third is highly likely also to instantiate that technique. The provenance of the objects is recorded as “Coptic Egyptian” on anecdotal evidence and without ascription of specific dates. If scientific dating were to establish that any of them approaches even the youngest age this might imply, the accepted date for the advent of crochet would require major revision.